Prognostic value of the serum creatinine/albumin ratio for 28-day mortality in heart failure: a retrospective cohort study - Hao Luo; Xinqi Chen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure (HF) is a global health challenge with high morbidity and mortality. The serum creatinine/albumin ratio (CAR), a marker of renal dysfunction and malnutrition, has shown prognostic value in other critical illnesses but remains underexplored in HF patients.MethodsThis retrospective cohort study included 1,893 HF patients hospitalized at the Fourth People's Hospital of Zigong, China, between December 2016 and June 2019. Cox proportional hazards models assessed the association between CAR and 28-day mortality. Dose-response relationship was assessed using restricted cubic spline analysis, Kaplan–Meier curves illustrated survival differences, and Receiver Operating Characteristic (ROC) analysis evaluated CAR's predictive performance.ResultsPatients with CAR ≥ 3.5 were older, had worse cardiac function, and had more comorbidities than those with CAR < 3.5.A linear relationship was observed between CAR and 28-day mortality. Each 1-unit increase in CAR was associated with a 14% higher mortality risk (HR: 1.14, 95% CI: 1.07–1.21, p < 0.001). ROC analysis showed that CAR had an AUC of 77.1%, which was slightly higher than creatinine alone (76.2%) and markedly better than BNP (68.0%) and albumin alone (64.9%).ConclusionIn patients with HF, CAR may serve as an independent predictor of 28-day mortality. Its ability to simultaneously reflect renal dysfunction, malnutrition, and inflammation highlights its potential as a valuable biomarker for risk stratification. Further multicenter, prospective studies are needed to confirm its clinical utility and investigate its role alongside other biomarkers in guiding personalized treatment strategies and improving patient outcomes.